Targeted UPLC-QqQ-MS/MS profiling of phenolic compounds for differentiation of monovarietal wines and corroboration of particular varietal typicity concepts. (1st December 2019) - Lukić, Igor; Radeka, Sanja; Budić-Leto, Irena; Bubola, Marijan; Vrhovsek, Urska
Highlights: UPLC-QqQ-MS/MS profiling of 58 phenols in 173 wines, 4 red and 6 white grape varieties. Many phenols as varietal markers, efficacy of differentiation by SLDA >95% in all cases. Potent differentiators: peonidin 3-(6″-acetyl)-glucoside and taxifolin for red, cis -piceid for white wines. Anthocyanin composition was useful for elucidating diverse typical colour attributes. trans -fertaric acid, isorhapontin, phlorizin, quercetin 3-rhamnoside, myricitrin were typical for Plavac mali red wine. Abstract: Targeted ultra-performance liquid chromatography with triple quadrupole mass spectrometric (UPLC-QqQ-MS/MS) profiling of phenolic compounds was utilised for varietal differentiation of 173 wines made from four red and six white grape varieties. Among 58 identified phenols many were found relevant as exclusive or partial discriminators between wines. Successful differentiation models were built by linear discriminant analysis with the percentage of correct classification higher than 95% in all cases, with peonidin 3-(6″-acetyl)-glucoside and taxifolin as the most potent differentiators between red, and cis -piceid between white monovarietal wines. Diverse typical colour attributes among the monovarietal wines were tentatively ascribed to the variations in the composition of monomeric anthocyanins. Plavac mali red wine exhibited the most specific composition, and its most typical samples were distinguished by the abundance in trans -fertaric acid, isorhapontin, phlorizin, quercetin 3-rhamnoside, and myricitrin. Despite positive correlations with particular astringent flavonols, the typical astringency of Plavac mali wine remained unresolved.